Exploring the Emergence of Community Support for School and Encouragement of Innovation for Improving Rural School Performance: Lessons Learned at Kitamburo in Tanzania - Ngalawa, Athanas August; Simmt, Elaine; Glanfield, Florence (Global Education Review, 2015)
This article describes a qualitative exploration of a primary school in a remote rural community of Tanzania, whose students showed promising performance in mathematics, as measured by the Primary School Leaving Examinations (PSLE). Case study methods were used to conduct research about the school and community in order to understand the dynamics that shape the school and village as community and communities. Interviews, focus groups, and observations were conducted. The paper identifies the role of village leadership in generating a learning community (Warren, 2005), that initiated community support of the school, which in turn prompted teachers’ innovations for developing in their work as professionals, that improved teaching and learning practices in mathematics and contributed to the noted promising performance on the PSLE. The article concludes that although school principals and teachers are regarded as keys in generating professional learning communities (DuFour, DuFour, & Eaker, 2008; Fullan, Hill &Crévola, 2006 ), under good community leadership communities may be essential catalysts in establishing and sustaining professional learning communities and contribute to school improvement.
KerkoCite.ItemAlsoKnownAs: 2129771:76XSWU4V 261495:MG4BUED8
Keywords: ⛔ No DOI found